Pengaruh Nursing Agency dan Dukungan Keluarga Terhadap Self-Care Behavior Penderita Hipertensi Di Masa Pandemi Covid-19 - Mahmudatun Ulya; Arif Setyo Upoyo; Agis Taufik (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2023)
Hypertension patients are among the populations who are more vulnerable to Covid-19 infection, necessitating extra care and consideration. Self-care is essential for the treatment of hypertension to be effective. The purpose of this study was to determine how hypertension patients' self-care practices during the Covid-19 epidemic were influenced by nursing agency and family support. Cross-sectional study design is used in this quantitative research. Using complete sample procedures, 71 hypertensive subjects participated in the study. The Patient Satisfaction with Nursing Care Scale (PSNCS), the Family Support Questionnaire, and the Hypertension Self-Care Profile (HBP-SCP): Behavior Scale are the instruments that were used. Results this analysis revealed a strong correlation (p0,001, r=0,621) between patients' self-care behavior and family support and a significant correlation (p0,001, r=0,781) between nursing agency and patients' self-care behavior. The most significant characteristic influencing patients with hypertension's self-care behavior is the nursing agency (Beta 0,432).